2008
DOI: 10.1651/07-2964.1
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Reproduction of the Portunid Crab Charybdis Bimaculata (Decapoda: Brachyura) in Tokyo Bay

Abstract: A B S T R A C TThe abundance, sex ratio, growth, sexual maturity, morphological sex dimorphism, and reproduction of the portunid crab Charybdis bimaculata was studied in Tokyo Bay, Japan, between November 2002 and October 2003. Relative abundance [inferred from catch-perunit-effort (CPUE)] was higher and lower during summer and winter months, respectively. The proportion of males varied between 0.2-0.5 throughout the year and the overall sex ratio was greatly biased toward females. The population had a unimoda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
16
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 42 publications
7
16
0
2
Order By: Relevance
“…Mann-Whitney test of carapace width and length of C. anisodon showed a significantly different (p<0.05) between males and females (Table 2). Body size (carapace width and length) of male was larger than females, and this is identical to those found in some other species of Charybdaris, such as C. feriatus (Dineshbabu 2011;Dash et al 2014), C. natator (Sumpton 1998; Sallam and Gab-Alla 2010; Vidhya 2016), C. bimaculata (Doi et al 2008), C. hellerii (Ozcan et al 2010;Sant'Anna et al 2012;Ferry et al 2017) and C. japonica (Fowler 2011;Wong 2013).…”
Section: The Number and Carapace Sizesupporting
confidence: 80%
“…Mann-Whitney test of carapace width and length of C. anisodon showed a significantly different (p<0.05) between males and females (Table 2). Body size (carapace width and length) of male was larger than females, and this is identical to those found in some other species of Charybdaris, such as C. feriatus (Dineshbabu 2011;Dash et al 2014), C. natator (Sumpton 1998; Sallam and Gab-Alla 2010; Vidhya 2016), C. bimaculata (Doi et al 2008), C. hellerii (Ozcan et al 2010;Sant'Anna et al 2012;Ferry et al 2017) and C. japonica (Fowler 2011;Wong 2013).…”
Section: The Number and Carapace Sizesupporting
confidence: 80%
“…Throughout the growth of brachyuran crabs, certain body structures, particularly the chelipeds in males and the abdomen in females, have been used by various researchers in studies on morphological maturity due to their functions in reproduction (see Hartnoll, 1978Hartnoll, , 1982Hartnoll, , 1985Pinheiro & Fransozo, 1993;Fernández-Vergaz et al, 2000;Corgos & Freire, 2006;Bertini et al, 2007;Hirose & Negreiros-Fransozo, 2007;Doi et al, 2008;Mclay & Van den Brink, 2009;Rasheed & Mustaquim, 2010;Sal Moyano et al, 2011). In these studies, significant changes in the allometric growth rates are usually correlated with morphological changes in such body structures between immature and mature phases, which might occur gradually over a series of moults or abruptly at a single moult (Hartnoll, 1978(Hartnoll, , 1982(Hartnoll, , 1985.…”
Section: Introductionmentioning
confidence: 99%
“…Despite several studies on relative growth and reproductive traits of brachyuran crabs (see Pinheiro & Fransozo, 1993;Flores & Negreiros-Fransozo, 1998;Mantelatto & Fransozo, 1999a, b;Fernández-Vergaz et al, 2000;Corgos & Freire, 2006;Hartnoll et al, 2006;Bertini et al, 2007;Hirose & Negreiros-Fransozo, 2007;Doi et al, 2008;Cobo & Alves, 2009;Mclay & Van den Brink, 2009;Bertini et al, 2010;Sal Moyano et al, 2011), little is known about the biology of leucosiid species, including P. lichtensteinii, P. mediterranea, and P. punctata throughout their range of distribution. Negreiros-Fransozo et al (1989) described the early larval development of P. mediterranea; Bertini et al (2001Bertini et al ( , 2010 reported on the spatial and temporal distribution of Persephona spp.…”
Section: Introductionmentioning
confidence: 99%
“…Examples in Brazil include the reproductive cycle of Callinectes danae Smith, 1869 (Costa & Negreiros-Fransozo 1998), fertility and reproduction of Arenaeus cribrarius Lamarck, 1818 (Pinheiro & Terceiro 2000), sexual and functional maturity of Chaceon affinis (A. Milne-Edwards & Bouvier, 1894) (Fernándes-Vergaz et al 2000), growth and reproduction of Charybdis bimaculata (Miers, 1886) (Doi et al 2008), physiological maturity and the relationship of growth and reproduction of Goniopsis cruentata (Latreille, 1802) (Cobo & Fransozo 2005) and reproductive period and size at maturity of Persephona mediterranea (Herbst, 1794) (Bertini et al 2010b).…”
Section: Introductionmentioning
confidence: 99%